Synthesis, formation and characterization of zirconium titanate (ZT) powders - Ananta S. (2014)
Zirconium titanate (ZrTiO4) powders have been prepared and characterised by differential thermal analysis (DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) techniques. The effect of calcination temperature, dwell time and heating/cooling rates on phase formation, morphology and particle size distribution of the powders are examined. The calcination temperature and dwell time have been found to have a pronounced effect on the phase formation and particle size of the calcined zirconium titanate (ZT) powders. It has been found that the minor phases of ZrO2 and TiO2 tend to form together with ZrTiO4, depending on calcination conditions. Optimisation of calcination conditions can lead to a single-phase ZrTiO4 in an orthorhombic phase. © 2002 Elsevier Science B.V. All rights reserved.